2012
DOI: 10.1021/jf300740d
|View full text |Cite
|
Sign up to set email alerts
|

NMR, HPLC-ESI-MS, and MALDI-TOF MS Analysis of Condensed Tannins from Delonix regia (Bojer ex Hook.) Raf. and Their Bioactivities

Abstract: The structures of the condensed tannins isolated from leaf, fruit, and stem bark of Delonix regia (Bojer ex Hook.) Raf. have been investigated with (13)C nuclear magnetic resonance ((13)C NMR) and high performance liquid chromatography electrospray ionization mass spectrometry (HPLC-ESI-MS) coupled with thiolysis and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) analyses. The results showed that these condensed tannins from D. regia possessed structural heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 35 publications
1
69
0
Order By: Relevance
“…Some few reports exist in plants, including heteropolymers up to trimers in the leaves of Fagus silvatica [25] and Senna alata [26]. Studies in Rumex acetosa leaves showed predominance 5:1 of procyanidin over the propelargonidin units [27]; and while heteropolymers have been reported in Delonix regia leaves, only procyanidins existed in its bark [28]. In Acacia confuse and Casuarina equisetifolia bark, heteropolymers occurrence has been reported with predominance of procyanidins over propelargonidins [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Some few reports exist in plants, including heteropolymers up to trimers in the leaves of Fagus silvatica [25] and Senna alata [26]. Studies in Rumex acetosa leaves showed predominance 5:1 of procyanidin over the propelargonidin units [27]; and while heteropolymers have been reported in Delonix regia leaves, only procyanidins existed in its bark [28]. In Acacia confuse and Casuarina equisetifolia bark, heteropolymers occurrence has been reported with predominance of procyanidins over propelargonidins [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The 13 C NMR spectra of the condensed tannins were recorded on a Varian Mercury-600 spectrometer (Palo Alto, CA, USA) at 150 MHz as described in reference [31].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies describe the use of NMR in the identification of diff fi erent ff ff compounds present in natural matrices: epimeric forms of fl avone glycosides fl [219]; tannin isomers [220]; anthocyanins [221]; rosmarinic acid [222]; para-hydroxy methyl benzoate glucoside, cycloeucalenol cis-ferulate, cycloeucalenol trans-ferulate, trans-ferulic acid, trans-ferulic acid methyl ester, cis-ferulic acid, cis-ferulic acid methyl ester, methyl caffeate, vanillic ff ff aldehyde and para-hydroxy benzaldehyde [223]; 9-O-(3-carboxymethyl-4-(p-formylstyryl))hydroxybutanoic acid, 2-hydroxy-3-methoxycaffeic ff ff acid 5-O-β-D-glucopyranoside and 3 -O-methyl-4 -O-(4-O-galloyl-α-Lrhamnopyranosyl) ellagic acid [224].…”
Section: Structure Elucidation Of Individual Antioxidant Compoundsmentioning
confidence: 99%